Data Engineering for Dynamic and Secure Blockchain Networks in AI Applications (International Journal of Information and Electronics Engineering, 2023)
In the evolving landscape of Artificial Intelligence (AI), the need for dynamic, secure, and transparent data infrastructures has become more critical than ever. Blockchain technology, known for its decentralized, tamper-proof nature, has emerged as a promising solution to  address trust